2015
DOI: 10.1007/s00246-015-1210-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Copy Number Variations in Isolated Tetralogy of Fallot

Abstract: Tetralogy of Fallot (ToF) is one of the most common and severe congenital heart defects (CHD). Recently, unbalanced structural genomic variants or copy number variations (CNVs) were proposed to be involved in the etiology of many complex diseases, including CHDs. The aim of this study was to investigate the frequency of CNVs in a region with a high density of CNVs, 22q11.2, and other regions with CHD-related genes in a sample of 52 Mexican mestizo patients with isolated ToF and negative fluorescence in situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…This finding agrees with the previous reports, where detection rate range from 0.4 to 8.5%. 11,[13][14][15]18 22q11DupS identification is reported less commonly, ranging from 0.7 to 2.5%, 13,14,16 very similar to our own (0.5%). Identification of 22q11DupS has been increased due to screening techniques currently used.…”
Section: Discussionsupporting
confidence: 86%
“…This finding agrees with the previous reports, where detection rate range from 0.4 to 8.5%. 11,[13][14][15]18 22q11DupS identification is reported less commonly, ranging from 0.7 to 2.5%, 13,14,16 very similar to our own (0.5%). Identification of 22q11DupS has been increased due to screening techniques currently used.…”
Section: Discussionsupporting
confidence: 86%
“…The results showed that the expression of human GATA4, NKX2.5, TBX1, HAND2, SMYD1 and MEF2C was significantly downregulated compared with that in the control ( Fig. 2A-F), which is similar to the cases for GATA4, NKX2.5 and TBX1 observed in other studies 28,29 . Compared with the control samples, the mean expression of ISL1 was higher than that of the control group, which was significant ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…NuRD complex target specificity can be conferred by the association of components of the NuRD complex with tissue-specific cofactors that target the complex to a defined set of loci. Factors include three proteins associated with congenital heart disease: FOG-2, TBX5, and TBX20 ( 3 , 19 32 ). Consistently, mutations in CHD4 have been found to be causative to congenital heart disease, including atrial and ventricular septal defects ( 4 ).…”
mentioning
confidence: 99%